Research on gradient aging behaviors of asphalt and decay characteristics of its properties under complex UV radiation conditions based on component diffusion and aging kinetics theory. - Hengbin Liu; Zhongnan Tian; Ying Fang; Zhengqi Zhang; Yulong Zhao; Peng Hu; Kun Wang (PLoS ONE)
To gain a more comprehensive understanding of UV aging process of base asphalt and SBS polymer modified asphalt, the gradient aging behaviors of asphalt and decay characteristics of their properties under different UV radiation conditions were investigated. Initially, different types of asphalt film specimens were subjected to UV aging test under complex radiations. Then, the aged asphalt samples were stripped layer by layer through the stratified elution method. And frequency scanning test for asphalt from different layers were carried out. Subsequently, the gradient UV aging behaviors and aging depth of asphalt were analyzed with G*, G*AI and diffusion coefficient D. Finally, UV aging kinetics equations of asphalt under different UV radiations were established to analyze the decay characteristics of its properties. Results show that UV aging process of asphalt exists the significant gradient aging distribution phenomenon, which starts from the surface of asphalt and gradually develops to the deeper layer of asphalt. Relationship between the aging depth of asphalt and aging times be characterized by a two-stage model, with the logarithm model in the early stage and the linear stage in the later stage. Enhancement of radiation intensity and aging temperature will both lead to the increase in the D values of asphalt, thus making the UV aging gradient behaviors of asphalt more obvious. Results of aging kinetics equations show that UV aging process of asphalt also follows the two-stage reaction phenomenon. And aging time of 24 hours can be set as the criteria to distinguish between the two-stage reaction zones. Meanwhile, enhancement of radiation intensity and aging temperature can also both lead to the increase in the aging reaction rate of asphalt. By contrast, radiation intensity has a greater effect on the UV aging reaction rate of asphalt than aging temperature, indicating that radiation intensity dominates the main effect in the degradation process of asphalt's UV aging properties.